1993
DOI: 10.1177/073401689301800202
|View full text |Cite
|
Sign up to set email alerts
|

Capital Punishment and the Deterrence of Violent Crime in Comparable Counties

Abstract: A matching process identified 293 pairs of counties in the United States that share 45 percent or more of their borders across a state line. Data from the 1988 County and City Data Book were then used to examine social, demographic, and economic differences within these matched pairs, with the difference in the violent crime rate in each pair employed as the dependent variable. Three variables reflecting the existence and use of capital punishment in the two states represented in each matched pair-the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Following Ehrlich (1975), a number of studies have found evidence supporting a deterrent effect of the death penalty (Cloninger, 1977;Deadman and Pyle, 1989;Ehrlich, 1977;Ehrlich and Liu, 1999;Layson, 1985;Mocan and Gittings, 2001). A far larger set of studies have failed to ®nd deterrent effects of capital punishment (e.g., Avio, 1979Avio, , 1988Bailey, 1982;Cheatwood, 1993;Forst, Filatov, and Klein, 1978;Grogger, 1990;Leamer, 1983;Passell and Taylor, 1977). 1 Although only one small piece of the broader literature on the issue of We would like to thank Austan Goolsbee for comments and criticisms.…”
Section: Introductionmentioning
confidence: 99%
“…Following Ehrlich (1975), a number of studies have found evidence supporting a deterrent effect of the death penalty (Cloninger, 1977;Deadman and Pyle, 1989;Ehrlich, 1977;Ehrlich and Liu, 1999;Layson, 1985;Mocan and Gittings, 2001). A far larger set of studies have failed to ®nd deterrent effects of capital punishment (e.g., Avio, 1979Avio, , 1988Bailey, 1982;Cheatwood, 1993;Forst, Filatov, and Klein, 1978;Grogger, 1990;Leamer, 1983;Passell and Taylor, 1977). 1 Although only one small piece of the broader literature on the issue of We would like to thank Austan Goolsbee for comments and criticisms.…”
Section: Introductionmentioning
confidence: 99%
“…Initial analysis of capital punishment came in the form of normative, positivist research conducted in the 1980s and 1990s by geographer Keith Harries and Derral Cheatwood, a criminologist (Cheatwood, 1993; Harries, 1988, 1992, 1993, 1995; Harries & Cheatwood, 1997). Their studies approach the subject empirically and present maps, tables, and charts that help to visualize spatio‐temporal patterns of capital punishment.…”
Section: How To Approach the Geographies Of Capital Punishmentmentioning
confidence: 99%
“…Perhaps it is this widening gap between law and enforcement that has spurred the PNG government's recent reintroduction of the death penalty for crimes of extreme violence (Callick 2013). While symbolic of the PNG state's desire to assume control of both life and death (something which exceeds its grasp) it is highly unlikely that the imposition of the death penalty will be effective in reducing sorcery accusation-related violence, given its proven ineffectiveness in reducing violent crime in other jurisdictions (Cheatwood 1993). Rather than reducing sorcery and witchcraft accusation-related violence, every intervention based on more law and punishment merely widens the gap between 'law on the books' and the state's capacity to regulate violence in practice.…”
Section: The Application Of Human Rights Law To Sorcery Accusation-rementioning
confidence: 99%